Dental avoidance among adolescents – a retrospective case –control study based on dental records in the public dental service in a Swedish county. (2nd January 2019) - Fägerstad, Anida; Lundgren, Jesper; Windahl, Jenny; Arnrup, Kristina
Abstract: Objective: This study aimed to investigate the occurrence of missed dental appointments among 16–19-year-old adolescents in a Swedish county. A second aim was to explore associations between background and concomitant factors and missed appointments and to investigate if these associations differed between areas with different sociodemographic profiles. Materials and methods: A list of booked, and missed, appointments for 10, 158 individuals during 2012 was used for assessments. Based on the total sample, 522 cases with, and 522 matched controls without, dental avoidance behavior in 2012 were identified. Data on previous missed and cancelled appointments, oral health status, dental treatment, fear or behavior problems, and medical, and, where available, psychosocial or lifestyle factors were extracted from the dental records using a preset protocol covering the period 2009–2012. Results: In 2012, 13.1% of 23, 522 booked appointments were missed, with a higher proportion of missed appointments among boys than girls. Cases with avoidance behavior more often had a record of sociodemographic load and dental fear or behavior management problems. They also had more oral health problems, more invasive dental treatments, and, in the past, more missed and canceled appointments. Conclusion: To enable good oral health and continued regular dental care, we need to pay more attention to adolescents' individual situation and be observant of early signs of avoidance.